Basin‐Scale Variations in Labile Dissolved Phosphoric Monoesters and Diesters in the Central North Pacific Ocean. Issue 5 (13th May 2019) - Yamaguchi, Tamaha; Sato, Mitsuhide; Hashihama, Fuminori; Ehama, Makoto; Shiozaki, Takuhei; Takahashi, Kazutaka; Furuya, Ken
Abstract: Labile dissolved phosphoric esters act as important phosphorus sources for microorganisms in the low‐phosphate oligotrophic ocean. Despite the significant role of labile dissolved phosphoric esters, previous studies have only focused on phosphoric monoesters, and the spatial distribution and dynamics of phosphoric ester species, including diesters, remain unclear. Thus, we aimed to elucidate basin‐scale variations in both monoesters and diesters and their role on microorganisms particularly in terms of diazotrophs. This is the first study to report the concentrations of these phosphoric esters in low‐ to middle‐latitudinal areas of the central North Pacific Ocean, concurrent with their hydrolysis rates. Hydrolysable monoester and diester concentrations ranged from undetectable levels to 40 nM, and their sum accounted for <11% of dissolved organic phosphorus on average. While monoester concentrations were significantly low in the low phosphate (<100 nM) region, there was no obvious trend between diester and phosphate concentrations. Monoesterase and diesterase activities showed significantly high values under low phosphate conditions when normalized by chlorophyll a concentrations. This indicated that both esters served as alternative phosphorus sources for microbial communities including phytoplankton. Diester concentrations and diesterase activities were positively correlated with nitrogen fixation activities, whereas such relationships were not observed for monoester concentrations and monoesterase activities. Thus, our results suggest that diesters have high affinity to diazotrophs compared with monoesters, which are utilized by a broad spectrum of microorganisms. Plain Language Summary: Phosphate, the most commonly utilized form of phosphorus, is scarce in some oceanic regions, such as subtropical regions. In such regions, microbes are known to utilize phosphoric esters instead, because some esters are easily hydrolyzed. However, limited quantitative data on these hydrolysable esters are available to date, and basic information is still lacking. Thus, we examined the concentrations and hydrolysis rates of representative hydrolysable esters (monoesters and diesters) in the central North Pacific Ocean. The results showed that both ester concentrations varied among a narrow and low range (under detection limit to 40 nM), although the distribution patterns were different between monoesters and diesters. This new information will contribute to a better understanding of why and how they are distributed in such a manner. We also found an interesting link between diesters and nitrogen fixation, a globally important process in marine ecosystems, suggesting that diesters play a significant role on nitrogen fixing organisms. Therefore, our study indicates that diesters may have a greater significance in the ocean than previously thought. Key Points: We present the first report on basin-scale variations in phosphoric monoesters and diesters at the nanomolar level in the central North Pacific Esterase activity showed that monoesters and diesters were utilized as P sources by microbes that were not severely phosphorus‐limited N fixation was correlated with diester concentrations and diesterase activity, showing affirmative diester utilization by diazotrophs